(Invited) Exploring Sub-Second and Sub-Micron X-Ray Tomographic Imaging of Liquid Water in PEFC Gas Diffusion Layers. (3rd July 2019) - Xu, Hong; Marone, Federica; Nagashima, Shinya; Nguyen, Hai; Kishita, Keisuke; Büchi, Felix N.; Eller, Jens
Abstract : In the last decade X-ray tomographic microscopy (XTM) has become a powerful 3D characterization technique for polymer electrolyte fuel cells. In order to improve both spatial and temporal resolution for operando polymer electrolyte fuel cell (PEFC) XTM imaging, the high magnification white beam microscope capabilities at the TOMCAT beamline of the Swiss Light Source (SLS) at Paul Scherrer Institut were explored. The image quality is evaluated in terms of contrast-to-noise ratio and in-situ water detectability for three different beam configurations and two magnifications. High water detectability levels can be achieved with a voxel size of 0.4 µm at 0.25 s scan time.